Georg Simmel's Philosophy of Money Concept in the Digital Era: The Role of Money in the Social Life of Content Creators - Agri Famela, Jely (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
The digital era has significantly reshaped social interactions, production processes, and the construction of social identities, particularly through the emergence of content creators on platforms like TikTok and Instagram. This study aims to explore how money, as conceptualized by Georg Simmel, influences the social lives of content creators and how it serves as both a material and symbolic force within digital spaces. The urgency of this research lies in the growing complexity of monetization practices that blur the boundaries between economic value and social recognition. Using a descriptive qualitative approach with a literature review method, this study critically analyzes various scholarly articles, books, and relevant digital content to synthesize theoretical insights with contemporary phenomena. The findings reveal that the objectification of social relationships through money aligns with the commodification of content and the increasing pressure creators face to meet audience expectations and algorithmic demands. While money provides creators with economic opportunities and social recognition, it simultaneously constrains their creativity and authenticity. This duality raises important questions about the implications of monetization on social values and identity formation in the digital realm. The study contributes to theoretical discussions on Simmel"™s philosophy of money by highlighting its relevance to understanding power dynamics, commodification, and social hierarchies in the digital economy.